Rockspelande unga kvinnor — mediafenomen och feministisk praxis - Nordström, Marika (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2004)
Why is there at present a specific interest in young women who play rock music? Since rock has been a male dominated arena, is the combination of rock and women a symbol for a step forward to (greater) gender equality? Or is this interest based on the fact that women who play rock are a marginalized, although growing, group in our society? I analyse this phenomenon by looking at media presentations such as commercials as well as my own interviews. My thesis focuses on young, female musicians who are active on the amateur popular music arena in Sweden today. Furthermore, they are all connected to two associations, whose main purpose is to make it easier for young women who want to enter the popular music arena. This entails that questions of feminism are important. There is a specific focus on the women as female musicians, which also manifests itself in concepts such as "girl bands/girl groups", which often tend to marginalize them and raise the issue of their competence.